Considere Las Siguientes Matrices
Considere Las Siguientes Matrices
Considere Las Siguientes Matrices
0 = 𝐿31 ∗ 𝑈11 −1 = 𝐿31 ∗ 𝑈12 + 𝐿32 ∗ 𝑈22 1 = 𝐿31 ∗ 𝑈13 + 𝐿32 ∗ 𝑈23 + +𝑈33
0 = 𝐿31 ∗ 1 −1 = 0 ∗ 2 + 𝐿32 ∗ 6 1
1 1 = 0 ∗ 2 + (− ) (−1) + 𝑈33
𝐿31 = 0 6
𝐿32 = − 5
6 𝑈33 =
6
MATRIZ L
10 0
21 0
𝐿=[ 1 ]
0 − 1
6
MATRIZ U
1 −1 2
0 6 −1
𝑈=[ 5]
0 0
6
𝑨 = 𝑷𝑳𝑼
𝑨
𝑷=
𝑳𝑼
1 −1 2
[2 1 3]
𝑃= 0 −1 1
1 0 0 1 −1 2
[2 1 0 ] ∗ [0 6 −1]
1 5
0 −6 1 0 0
6
𝟏 𝟎 𝟎
𝑷 = [𝟎 −𝟏 𝟏]
𝟎 𝟏 𝟎
𝟎 𝟏 𝟏
𝑨 = [𝟏 −𝟐 −𝟏]
𝟏 −𝟏 𝟏
0 1 1
𝐴 = [1 −2 −1]
1 −1 1
𝐶2 = 𝐶1 → 𝐶2
1 0 1
𝐴 = [−2 1 −1]
−1 1 1
METODO LU
𝑈11 = 1
𝑈12 = 0
𝑈13 = 1
−2 = 𝐿21 ∗ 𝑈11 1 = 𝐿21 𝑈12 + 𝑈22 −1 = 𝐿21 𝑈13 + 𝑈23
−2 = 𝐿21 ∗ 1 1 − 𝐿21 𝑈12 = 𝑈22 −1−𝐿21 𝑈13 = 𝑈23
𝐿21 = −2 1 + 2(0) = 𝑈22 𝑈23 = −1 + 2(1)
𝑈22 = 1 𝑈23 = 1
−1 = 𝐿31 ∗ 𝑈11 1 = 𝐿31 ∗ 𝑈12 + 𝐿32 ∗ 𝑈22 1 = 𝐿31 ∗ 𝑈13 + 𝐿32 ∗ 𝑈23 + 𝑈33
−1 = 𝐿31 ∗ 1 1 = −1 ∗ 0 + 𝐿32 ∗ 1 1 = −1 ∗ 1 + (1)(1) + 𝑈33
𝐿31 = −1 𝐿32 = 1 𝑈33 = 1
MATRIZ L
1 0 0
𝐿 = [−2 1 0]
−1 1 1
MATRIZ U
1 0 1
𝑈 = [0 1 1]
0 0 1
𝑨 = 𝑷𝑳𝑼
𝑨
𝑷=
𝑳𝑼
1 0 1
[−2 1 −1]
𝑷= −1 1 1
1 0 0 1 0 1
[−2 1 0] ∗ [0 1 1]
−1 1 1 0 0 1
𝟎 𝟏 𝟎
𝑷 = [𝟏 𝟎 𝟎]
𝟎 𝟎 𝟏
METODO LU
MATRIZ L
1 0 0
3
1 0
𝐿= 2
3
[2 1 1]
MATRIZ U
2 1 −1
15
𝑈 = [0 9/2 ]
2
0 0 −4
1 0 0
3 2 −1 1
1 0 15
𝑳𝑼 = 2 ∗ [0 9/2 ]
3 2
[2 1 1] 0 0 −4
𝟐 𝟎 𝟎 𝟎
𝟏 𝟏. 𝟓 𝟎 𝟎
𝑨=[ ]
𝟎 −𝟑 𝟎. 𝟓 𝟎
𝟐 −𝟐 𝟏 𝟏
METODO LU
0 = 𝐿31 ∗ 𝑈11 −3 = 𝐿31 ∗ 𝑈12 + 𝐿32 ∗ 𝑈22 0.5 = 𝐿31 ∗ 𝑈13 + 𝐿32 ∗ 𝑈23 + 𝑈33 0 = 𝐿31 ∗ 𝑈14 + 𝐿32 ∗ 𝑈24 + 𝑈34
0 = 𝐿31 ∗ 2 3 0.5 = 0 ∗ 0 + (2)(0) + 𝑈33 0 = 0 ∗ 0 + 2 ∗ 0 + 𝑈34
3 = 0 ∗ (0) + 𝐿32 ∗ 1
𝐿31 = 0 2 𝑈34 = 0
𝐿32 = 2 𝑈33 =
2
2 = 𝐿41 ∗ 𝑈11 −2 = 𝐿41 ∗ 𝑈12 + 𝐿42 ∗ 𝑈22 1 = 𝐿41 ∗ 𝑈13 + 𝐿42 ∗ 𝑈23 + 𝐿43 ∗ 𝑈33 1 = 𝐿41 ∗ 𝑈14 + 𝐿42 ∗ 𝑈24 + 𝐿43
2 = 𝐿41 ∗ 2 1 1 ∗ 𝑈34 + 𝑈44
−2 = 1 ∗ 0 + 𝐿42 ∗ 1 = 1 ∗ 0 + (−4) ∗ 0 + 𝐿43 ∗
𝐿41 = 1 2 2 1 = 1 ∗ 0 + (−4) ∗ 0 + 2 ∗ 0
𝐿42 = −4 𝐿43 = 2 + 𝑈44
𝑈44 = 1
MATRIZ L
𝟏 𝟎 𝟎 𝟎
0.5 𝟏 𝟎 𝟎
𝑳=[ ]
0 2 𝟏 𝟎
1 −4 2 𝟏
MATRIZ U
2 0 0 0
𝟎 1.5 0 0
𝑼=[ ]
𝟎 𝟎 0.5 0
𝟎 𝟎 𝟎 1
𝟏 𝟎 𝟎 𝟎 2 0 0 0
0.5 𝟏 𝟎 𝟎 𝟎 1.5 0 0
𝑳𝑼 = [ ]∗[ ]
0 2 𝟏 𝟎 𝟎 𝟎 0.5 0
1 −4 2 𝟏 𝟎 𝟎 𝟎 1